414 The prognostic impact of clinical and uterine factors in stage I endometrial cancer with negative lymph-vascular space invasion. (18th September 2019) - Brandt, B; Basaran, D; Shepherd, C; Ali, N; Thompson, E; Leong, K; Moon, A; Kuznicki, M; Leitao, MM; Abu-Rustum, NR; Mueller, JJ
Abstract : Objectives: To evaluate the impact of depth of invasion (DOI) and histology on survival of patients with stage I endometrial cancer (EC) with negative lymph-vascular space invasion (LVSI). Methods: All patients with stage I EC, negative LVSI and negative peritoneal washings, who underwent surgical staging at our institution between 01/2006–12/2016 were retrospectively reviewed. Appropriate statistical tests were employed. Results: We identified 1458 patients: median age 60 years (range, 27–92), median BMI 30 (range, 15–68), diabetes mellitus (DM)- 12%, invasion<50%- 96%, invasion≥50%- 4%, grade 1–2- 79%, grade 3- 21%, endometrioid- 85%, non-endometrioid- 15%, adjuvant radiotherapy- 30%, adjuvant chemotherapy- 12%. Median follow-up time was 29 months (range, 1–149). Overall 2-year disease specific survival rate (DSS) was 98.6% (SE 0.4%). On univariable analysis, non-endometrioid histology was associated with worse DSS compared with endometrioid histology (95.4% [SE 1.5%] vs 99.3% [SE 0.3%], p=0.001). DOI, race, BMI and surgical approach (minimally invasive vs open) did not correlate with DSS. On multivariable analysis, grade, DM and age were the only independent factors significantly associated with DSS (grade 3 vs grade 1–2: DSS 95.3% [SE 1.3%] vs 99.6% [SE 0.2%], p<0.001, HR 6.7 [95% CI 2.6–17.2]; DM vs non-DM: DSS 98.0% [SE 1.4%] vs 98.6% [SE 0.4%], p=0.001, HR 2.7 [95% CI 1.3–5.6]; age≥65 vs age<65: 97.8% [SE 0.8%] vs 99.0% [SE 0.4%], p<0.001, HR 2.3 [95% CI 1.2–4.5]). Conclusions: Disease specific survival of patients with stage I endometrial cancer without lymph-vascular invasion is determined by histologic grade, diabetes mellitus and age, but not by depth of invasion.